NUMERICAL SOLUTION OF TEMPERATURE DEPENDENT THERMAL CONDUCTIVITY ON MHD FREE CONVECTION FLOW WITH JOULE HEATING ALONG A VERTICAL WAVY SURFACE (Journal of Mechanical Engineering, 2014)
Temperature dependent thermal conductivity on magnetohydrodynamic (MHD) free convective flow of viscous incompressible fluid with Joule heating along a uniformly heated vertical wavy surface has been investigated numerically. The governing nonlinear boundary layer equations are mapped into a domain of a vertical flat plate and solved by an implicit finite difference method known as Keller-box scheme. The skin friction coefficient, the rate of heat transfer in terms of local Nusselt number, the stream lines and the isotherms are reported for different parameter combinations. DOI: http://dx.doi.org/10.3329/jme.v44i1.19497